Shadow scale - Hartman, Rachel (New York : Random House, 2015)
In the kingdom of Goredd, Seraphina - half-dragon and half-human - is reluctantly drawn into the politics of her world. When war breaks out between the dragons and humans, she must travel the lands to find those like herself, for she has an inexplicable connection to all of them, and together they will be able to fight the dragons in powerful, magical way.
Keywords: Dragons -- Fiction; Fantasy fiction